Acute Ischemic Stroke Treatment, Part 2: Treatment “Roles of Capillary Index Score, Revascularization and Time” - Al-Ali, Firas; Elias, John J.; Filipkowski, Danielle E. (Frontiers in Neurology, 2015)
Due to recent results from clinical intra-arterial treatment for acute ischemic stroke (IAT-AIS) trials such as the interventional management of stroke III, IAT-AIS and the merit of revascularization have been contested. Even though intra-arterial treatment (IAT) has been shown to improve revascularization rates, a corresponding increase in good outcomes has only recently been noted. Even though a significant percentage of patients achieve good revascularization in a timely manner, results do not translate into good clinical outcomes (GCOs). Based on a review of the literature, the authors suspect limited GCOs following timely and successful revascularization are due to poor patient selection that led to futile and possibly even harmful revascularization. The capillary index score (CIS) is a simple angiography-based scale that can potentially be used to improve patient selection to prevent revascularization being performed on patients who are unlikely to benefit from treatment. The CIS characterizes presence of capillary blush related to collateral flow as a marker of residual viable tissue, with absence of blush indicating the tissue is no longer viable due to ischemia. By only selecting patients with a favorable CIS for IAT, the rate of GCOs should consistently approach 80–90%. Current methods of patient selection are primarily dependent on time from ischemia. Time from cerebral ischemia to irreversible tissue damage seems to vary from patient to patient; so focusing on viable tissue based on the CIS rather than relying on an artificial time window seems to be a more appropriate approach to patient selection.